Pengembangan Usaha bagi Mantan TKI di Kecamatan Donomulyo Kabupaten Malang: Business Development for Former Indonesian Migrant Workers in Donomulyo District, Malang Regency - Latifah, Sri Wahjuni; Jati, A Waluya; Retna R, Erna (Universitas Muhammadiyah Sidoarjo, 2016)
Research of potential business for TKI at district Donomulyo Malang. The purpose of this research is to know the characteristics of the former TKI social aspects, culture and economy. Further is analyzing the potential of natural resources and supporting resources providing information fundamental to strategy the development. Further, makes informatian about the factors are considered in the investment decision making in the area. Informan this study is TKI, goverment officials, and Manager of KUD. The data are collected with interviews, questionnaires, FGD and copy related data. Data analysis was perfomed with several stages, : analysis of validit, reliabilitas discriptive statistical analysis and analysis Cluster of matrix. Next domain analysis is conducted to determine the factors that need to be considered in making investment decisions. The results showed that TKI Donomulyo Malang has characteristics social, cultural was highly, but characteristics economic was low. In accordance with the characteristics skill of former TKI and its natural resources the the potential of the relevant business is supporting the Tourism Beaches and Cave.